Increased use of primary care during 6 years of prodromal schizophrenia. (13th June 2016) - Nørgaard, HCB.; Søndergaard Pedersen, H.; Fenger‐Grøn, M.; Mors, O.; Nordentoft, M.; Vestergaard, M.; Munk Laursen, T.
Abstract : Background: Early diagnosis is important for the course of schizophrenia. Aim: To investigate whether prodromal symptoms of schizophrenia lead to increased use of primary care. Method: A register‐based cohort study of 21 894 cases with incident schizophrenia and 437 880 matched controls. Results: Cases used daytime primary care 43% more than controls during the 6 years before diagnosis (IRR = 1.43; 95% CI: 1.39; 1.48) and 132% more during the last 2 months (IRR = 2.32; 95% CI: 2.27; 2.37), and 34% (IRR = 1.34; 95% CI: 1.23; 1.48) vs. 374% more for out‐of‐hours services (IRR = 3.74; 95% CI: 3.52; 3.98). Six years before index diagnosis, 30% of cases had at least one psychiatric contact without being diagnosed with schizophrenia, increasing to 75% 1 month before diagnosis. Conclusion: Increased help‐seeking behaviour was seen at least 6 years before index diagnosis, suggesting a 'window' for earlier diagnosis of prodromal schizophrenia.